Comparison of pre-operative bilirubin level in simple appendicitis and perforated appendicitis - Vaziri, Mohammad (Iran University of Medical Sciences, 2013)
BACKGROUND: Delay in diagnosis and treatment of perforated appendicitis may cause life-threatening complications.The aim of this study was to determine and compare pre-operative total and direct bilirubin levels incases of simple and perforated acute appendicitis in order to improve the clinical decision making. METHODS: This prospective observational study included eighty patients who underwent open appendectomy,during a one-year period from March 2010 to March 2011 in the surgical department of Hazrat-e-Rasool AkramHospital, an academic teaching hospital in Tehran- Iran. Pre-operative total and direct levels of bilirubin werecompared in two groups of histologically proved appendicitis (simple and perforated), each including 40 patients. RESULTS: Eighty patients who underwent open appendectomy including 70% men and 30% women with a meanage of 34±11 years in Group I (perforated appendicitis) and 47.5% women and 52.5% men with a mean age of33±14 in Group II (simple appendicitis) were included in this study. The mean bilirubin levels were higher forpatients with perforated acute appendicitis compared to those with a non-perforated simple appendicitis(1.04±05 mg/dl vs 0.7±0.1 mg/dl) and this difference is highly significant (p<0.01). CONCLUSION: Assessment of preoperative total bilirubin is useful for the differential diagnosis of perforatedversus acute simple appendicitis and total bilirubin should be used as an independent parameter in the early diagnosisof appendix perforation